2010
DOI: 10.2147/jpr.s14209
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a rat model of metastatic prostate cancer bone pain

Abstract: Purpose:The objectives of this study were to establish and characterize a novel animal model of metastatic prostate cancer-induced bone pain.Methods:Copenhagen rats were injected with 106 MATLyLu (MLL) prostate cancer cells or phosphate-buffered saline by per cutaneous intra femoral injections into the right hind leg distal epiphysis. Over 13 days, rats progressively developed a tumor within the distal femoral epiphysis. On days 3, 7, 10, and 13 post injection, rats were subjected to the incapacitance and Rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…For instance, NCTC2472 bone cancers cells, MRMT-1 breast cancer cells, Lewis lung cancer cells, melanoma cancer cells, and prostate cancer cells have been employed to set up the animal model ( De Ciantis et al, 2010 ; Donovan-Rodriguez, Dickenson & Urch, 2005 ; Dore-Savard et al, 2010 ; Mao-Ying et al, 2006 ; Medhurst et al, 2002 ; Zhang & Lao, 2012 ). In our present study, our results showed that the values of pain behavior scoring were changed significantly on day 7 to day 9 in the K562 cells transplanted group, which is consistent with the behavioral changes of bone cancer pain in animal models transplanted with solid tumor cells ( De Ciantis et al, 2010 ; Dore-Savard et al, 2010 ; Mao-Ying et al, 2006 ; Medhurst et al, 2002 ; Zhang & Lao, 2012 ). To our knowledge, this is the first to employ leukemia cancer cells to build the bone pain animal model of leukemia, with minimal invasion in the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, NCTC2472 bone cancers cells, MRMT-1 breast cancer cells, Lewis lung cancer cells, melanoma cancer cells, and prostate cancer cells have been employed to set up the animal model ( De Ciantis et al, 2010 ; Donovan-Rodriguez, Dickenson & Urch, 2005 ; Dore-Savard et al, 2010 ; Mao-Ying et al, 2006 ; Medhurst et al, 2002 ; Zhang & Lao, 2012 ). In our present study, our results showed that the values of pain behavior scoring were changed significantly on day 7 to day 9 in the K562 cells transplanted group, which is consistent with the behavioral changes of bone cancer pain in animal models transplanted with solid tumor cells ( De Ciantis et al, 2010 ; Dore-Savard et al, 2010 ; Mao-Ying et al, 2006 ; Medhurst et al, 2002 ; Zhang & Lao, 2012 ). To our knowledge, this is the first to employ leukemia cancer cells to build the bone pain animal model of leukemia, with minimal invasion in the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Male Copenhagen rats (Harlan Laboratories Inc, Indianapolis, IN) weighing 200 to 250 g were randomly assigned to groups and induced as a model of CIBP as described in our previous study. 9 , 38 Briefly, CIBP rats were anesthetised with inhaled isoflurane (1%–5% in oxygen) and 5.0 × 10 6 MAT-LyLu (MLL) cells suspended in 0.05-mL phosphate-buffered saline (PBS) were injected into the distal epiphysis of the femur by manual rotation of a 25-gauge needle between the medial and lateral condyles. Sham injection (control) rats received an injection of 0.05-mL PBS only by the same procedures.…”
Section: Methodsmentioning
confidence: 99%
“…However, a major limitation of many currently utilized rodent models of PCIBP (Table 1) is that they involve intra-osseous injection of very large numbers of PCa cells which results in profound bone destruction (Lamoureux et al 2008; De Ciantis et al 2010; Kolosov et al 2011; Feeley et al 2006; Liepe et al 2005; Zhang et al 2005). This facilitates PCa cell metastasis formation in the adjacent soft tissues as well as the lungs and liver (Kolosov et al 2011; Liepe et al 2005; Luo et al 2006).…”
Section: Rodent Models Of Pcibpmentioning
confidence: 99%
“…This facilitates PCa cell metastasis formation in the adjacent soft tissues as well as the lungs and liver (Kolosov et al 2011; Liepe et al 2005; Luo et al 2006). The net result is the progressive deterioration of animal health, characterized by a significant temporal decrease in body weight relative to the sham-control groups (Zhang et al 2005; De Ciantis et al 2010), necessitating early euthanasia due to ethical concerns.…”
Section: Rodent Models Of Pcibpmentioning
confidence: 99%